Processing of gabi flour (Colocasia esculenta (L) Schott) - Echiverri, Rosalie Sabina R.; e Leon, Sonia Y. (1988)
A procedure for gabi flour production was developed using gabing tagalog corms (Colocosia esculenta (L.) Schott) as raw material. Sufficient blanching of the corms was observed after thirty minutes of blanching at 97-100 C. Dehydration of the gabi corms in a cabinet dryer at 180 F for three hours produced a flour of good quality. The flour had a moisture content of below 15% and a fat content below 2.0%. The color, odor, texture and general acceptability of the gabi flour were found to be significantly different from a commercial all-purpose wheat flour but the flour was generally acceptable. The flour was incorporated in butter cookies at 25, 50, and 75% levels of substitution for wheat flour. At 25% substitution, the cookies were found to be most acceptable. The degree of acceptability of the cookies was between like very much and like moderately. At 50 and 75% levels of substitution, the cookies were found to be less acceptable than the 25%. But all the cookie samples were generally accepted.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Taro